Development of a lipovitellin-based goldfish (Carassius auratus) vitellogenin ELISA for detection of environmental estrogens. (August 2015) - Wang, Jun; Wang, Wei; Zhang, Xiaona; Tian, Hua; Ru, Shaoguo
Highlights: An ELISA for goldfish Vtg was developed using purified lipovitellin (Lv). Lv is a lipoglycophosphoprotein with molecular mass of ∼420 kDa. Lv is a highly stable protein and has the same immunogenicity as Vtg. The estrogenic activity of monocrotophos pesticide was detected by the ELISA. The use of Lv as the standard could strengthen the robustness of the Vtg ELISA. Abstract: The susceptibility of vitellogenin (Vtg) to degradation is a major problem affecting the robustness of enzyme-linked immunosorbent assay (ELISA) for goldfish ( Carassius auratus ) Vtg. In this study, a phospholipoglycoprotein with molecular mass of ∼420 kDa was purified from goldfish egg extracts and it produced a single band corresponding to ∼112 kDa in SDS–polyacrylamide gel electrophoresis (SDS–PAGE). Additionally, the amino acid composition of the purified protein was comparable to that of lipovitellin (Lv) from other fish species. Thus, the purified protein was identified as goldfish Lv. Purified Lv and anti-Lv polyclonal antiserum were used to develop an ELISA with a detection range between 31.25 and 1000 ng mL − 1 . The intra- and inter-assay coefficients of variation were 6.45% and 7.08%, respectively. The immunological similarity between goldfish Vtg and Lv was confirmed by immunoelectrophoresis and Western blot. Goldfish Lv showed higher stability than Vtg after −80 °C storage, multiple freeze/thaw cycles, and heat treatment. Moreover, the use of treated Lv in the ELISA did not change the slopes of standard curves. Parallelism between the Lv standard curve and plasma dilution curves of vitellogenic females confirmed the validity of the assay for quantifying plasma Vtg. The Lv-based Vtg ELISA was further applied to evaluate the estrogenic activity of monocrotophos pesticide.